Understanding white collar crime - Strader, J. Kelly (San Francisco, California : LexisNexis, 2011)
White collar crime is primarily based upon a complex set of statutes. Understanding White Collar Crime provides the texts of the statutes, along with analyses of the statutes elements. Because many of these statutes are open to varying interpretations, the book also extensively discusses the main cases interpreting the statutes, including a large number of U.S. Supreme Court cases. Finally, the book discusses the significant policy issues that arise in white collar crime investigations and prosecutions, such as enforcement barriers and prosecutorial discretion.
Introduction to white collar crime -- Corporate and individual liability -- Conspiracy -- Mail fraud, wire fraud, and related offenses -- Securities fraud -- Computer crime -- Environmental crimes -- Bribery and gratuities -- Extortion -- False statements -- Perjury and false declarations -- Obstruction of justice -- Tax crimes -- Currency transaction reporting crimes -- Money laundering -- RICO -- Internal investigations and compliance programs -- Grand jury issues -- The right against compelled self-incrimination -- Civil actions, civil penalties, and parallel proceedings -- Sentencing -- Forfeitures.
Includes index.
Keywords: WHITE COLLAR CRIMES -- UNITED STATES